Pharmaceutical clinical services in basic care in a region of the municipality of São Paulo (Brazilian Journal of Pharmaceutical Sciences, 2018)
Pharmaceutical care has undergone several transformations in the health context over the years. Thus, the pharmacist has suffered a reconfiguration of his performance, mainly with the incorporation of clinical services and patient approach. The study analyzed the results of the implementation of pharmaceutical clinical services in Primary Health Care, through the use of indicators of supply, demand and productivity, clinical and process quality related to pharmaceutical care. We included all the clinical visits (n=1,833) performed to 1,080 users in 12 Basic Health Unit facilities from May to November 2016, of which 40.8% (n=748) were consultations in the establishments and 50.2% (n=1,085) home visits. Most patients (73.5%) were referred by team and 17.5% were captured through active search. Of the total workload, 12.5% were dedicated to pharmaceutical consultations and 20.0% to home visits. In total, we identified 3,078 pharmacotherapy-related issues, an average of 2.8 per patient, and 6,882 pharmaceutical interventions were performed, equivalent to 6.3 interventions per patient. The problem with adherence to pharmacotherapy and the intervention of medication counseling were the most found. Results reinforce the importance of pharmaceutical clinical services in identifying the control of the most prevalent health conditions and monitoring the therapeutic results associated with drug use.